Coffee Chemistry, as Microlearning Content for Public Courses at Universities’ Mooc System, A Preliminary Attempt - Surjani Wonorahardjo; Neena Zakia; Hanumi Oktiyani Rusdi; Irma Kartika Kusumaningrum (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2023)
An attempt to have a scientific course for the public from higher education institutions was done by preparing a good set of contents for one particular topic of interest, which is also a science topic. Coffee chemistry is the topic chosen and some content was developed, including videos, audio-embedded social media, infographics and motion graphics packed with 8 topics. The choice of coffee amongst many sciences’ topic is considered strategic in bringing science to all audiences of society. Science content must explain nature as the object in wholistic concepts, starting from smaller parts of each division, including chemistry. The microlearning approach is employed in the MOOC platform from The State University of Malang, Indonesia. This also is one of the three main tasks of higher education institutions which can be delivered in the MOOC system.